2020
DOI: 10.1126/sciadv.abb2210
|View full text |Cite
|
Sign up to set email alerts
|

Increased lysosomal biomass is responsible for the resistance of triple-negative breast cancers to CDK4/6 inhibition

Abstract: Inhibitors of cyclin-dependent kinases CDK4 and CDK6 have been approved for treatment of hormone receptor–positive breast cancers. In contrast, triple-negative breast cancers (TNBCs) are resistant to CDK4/6 inhibition. Here, we demonstrate that a subset of TNBC critically requires CDK4/6 for proliferation, and yet, these TNBC are resistant to CDK4/6 inhibition due to sequestration of CDK4/6 inhibitors into tumor cell lysosomes. This sequestration is caused by enhanced lysosomal biogenesis and increased lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Once trapped inside endolysosome, weak-base chemotherapeutic drugs can no longer reach the cytosolic compartment and the nucleus to exert their anticancer effects; processes linked to chemoresistance ( Zhitomirsky and Assaraf, 2017 ). Such trapped weak-base chemotherapeutic drugs can directly alter endolysosome structure and function, such as alteration in endolysosome pH and influence endolysosome-dependent signaling that results in enhanced endolysosome biogenesis ( Fassl et al, 2020 ). Alternatively, trapped weak-base chemotherapeutic drugs can be eliminated from the cell via an increase in the lysosomal exocytosis cellular process, which is known to be directly due to these drugs themselves ( Hrabeta et al, 2020 ).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Once trapped inside endolysosome, weak-base chemotherapeutic drugs can no longer reach the cytosolic compartment and the nucleus to exert their anticancer effects; processes linked to chemoresistance ( Zhitomirsky and Assaraf, 2017 ). Such trapped weak-base chemotherapeutic drugs can directly alter endolysosome structure and function, such as alteration in endolysosome pH and influence endolysosome-dependent signaling that results in enhanced endolysosome biogenesis ( Fassl et al, 2020 ). Alternatively, trapped weak-base chemotherapeutic drugs can be eliminated from the cell via an increase in the lysosomal exocytosis cellular process, which is known to be directly due to these drugs themselves ( Hrabeta et al, 2020 ).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Nonetheless, our analyses implicated upregulation of PI3K signaling via a PIK3CA p.E542K activating mutation, compensatory feedback signaling through mTORC2, activation of CDK2, sequestration by lysosomotropism, and compensatory signaling via the androgen receptor as possible resistance mechanisms. These analyses support switching from palbociclib to abemaciclib to counter the observed CDK2 activation (Hafner et al, 2019), use of enzalutamide to counter possible androgen mediated signaling as was done in Phase 3, and administration of a lysosomotropic drug such as hydroxychloroquine (Fassl et al, 2020) to counter sequestration of palbociclib or abemaciclib. Phase 1 treatment was terminated when blood biomarkers and CT measurement of several-but not all-metastatic lesions began to increase sharply.…”
Section: Discussionmentioning
confidence: 64%
“…This mechanism is suggested by the increase in lysosomes from Bx1 to Bx2 revealed by FIB-SEM ( Figures 6G, S6A). Drug sequestration via lysosomotropism has been implicated as a mechanism of resistance to palbociclib and other CDK4/6 inhibitors, indicating a possible role for these abundant vesicles in reducing therapeutic efficacy in this patient (Fassl et al, 2020;Llanos et al, 2019).…”
Section: Activation Of Cdk2 and Drug Sequestration Via Lysosomotropismentioning
confidence: 99%
“…In line with this, patients with FAT1-deficient tumors displayed a significantly shortened PFS compared to patients with FAT1-proficient tumors. Furthermore, a study by Cornell et al reported an increased expression of CDK6 being elicited by suppression of the TGF-β pathway via exosomal miRNA 432-5p [ 98 ].…”
Section: Other Mechanisms Of Cdk4/6 Inhibitor Resistancementioning
confidence: 99%
“…Finally, in triple-negative breast cancer (TNBC), an increased number of tumor cell lysosomes has been shown to mediate the intrinsic resistance to CDK4/6 inhibition [ 98 ]. Driven by their weak base properties, CDK4/6 inhibitors are sequestered into the enlarged lysosomal compartment and, therefore, are hindered from reaching their target, i.e., cyclin D-CDK4/6 complexes in the nucleus.…”
Section: Other Mechanisms Of Cdk4/6 Inhibitor Resistancementioning
confidence: 99%